2013
DOI: 10.1186/1475-2875-12-46
|View full text |Cite
|
Sign up to set email alerts
|

Physical condition and maintenance of mosquito bed nets in Kwale County, coastal Kenya

Abstract: BackgroundDespite the extensive ownership and use of insecticide-treated nets (ITNs) over the last decade, the effective lifespan of these nets, especially their physical integrity, under true operational conditions is not well-understood. Usefulness of nets declines primarily due to physical damage or loss of insecticidal activity.MethodsA community based cross-sectional survey was used to determine the physical condition and to identify predictors of poor physical condition for bed nets owned by individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
91
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(108 citation statements)
references
References 47 publications
(83 reference statements)
13
91
1
Order By: Relevance
“…It is likely that net owners underestimated the number of times each net was washed which is typically two or more times per year [19, 24]. The method of washing or drying, or the location of cooking (inside or outside the house) did not appear to impact deltamethrin levels.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that net owners underestimated the number of times each net was washed which is typically two or more times per year [19, 24]. The method of washing or drying, or the location of cooking (inside or outside the house) did not appear to impact deltamethrin levels.…”
Section: Discussionmentioning
confidence: 99%
“…The location of the holes on the LLINs is consistent with respondents' reports that securing of the LLINs at night as one of the major causes of the LLIN holes. 37 In addition, the survey teams observed that in rural households in Nampula LLINs are commonly secured at the bottom of the LLIN to the reed mat or other material used as a sleeping space. Further analysis is pending to identify potential associations of LLIN damage with factors including washing and frequency of use.…”
mentioning
confidence: 99%
“…In this study, 22.8% (23 of 101) of nets had holes Ͼ200 cm 2 , which could compromise the efÞcacy of these nets. However, attempts have recently been made to standardize comparisons of the physical condition of nets by calculating the pHI (Kilian et al 2011, World Health Organization 2011, Allan et al 2012, Batisso et al 2012, Mutuku et al 2013. It has been suggested that a poor or very poor net would have a total hole surface area Ͼ700 cm 2 (Allan et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, to provide a standard method for comparing net damage, the proportional hole index (pHI) was calculated. This calculation was published in the World Health Organization guidelines for monitoring LLIN durability in 2011 (World Health Organization 2011) and has been used in recent publica- tions (Kilian et al 2011, Allan et al 2012, Batisso et al 2012, Mutuku et al 2013). An average surface area for each hole size category was estimated to beÑthumb ϭ 4 cm 2 , Þst ϭ 36 cm 2 , and larger than a Þst ϭ 225 cm 2 (Kilian et al 2011).…”
Section: Methodsmentioning
confidence: 99%